Pensando a Museologia na Pós-modernidade: transformações críticas e pós-críticas. - Ribeiro Ferreira, Lorhana Serpa; Moletta Scheiner, Teresa Cristina (Museologia e Patrimônio, 2024)
Thinking about Museology requires examining the epistemic framework of contemporaneity, aiming to understand it as both a set of practices and a way of conceptualising reality, derived from a set of specific strategies for interpreting it. As a relatively new field of knowledge, with boundaries that still require clearer definition, Museology remains subject to partial narratives that hinder its comprehensive understanding. This article provides a general overview of the topic, preparing people for future, more in-depth investigations. Its contents are based on analyses developed for a Master's thesis defended in 2024 within the Postgraduate Programme in Museology and Heritage, at the Federal University of the State of Rio de Janeiro/Museum of Astronomy and Related Sciences (PPG-PMUS, UNIRIO/MAST). It proposes a reflection on how museological theory interprets reality, grounded in a brief contextualisation of the narratives of critical and post-critical theory. The aim is to contribute to the epistemic framework of Museology through exploratory, descriptive, and qualitative research. By investigating the epistemic condition of postmodernity, the paper seeks to examine the premises of what might be termed 'Critical Museology'. It also explores the concept of Post-Critical Museology by integrating recent studies by international scholars, addressing interdisciplinary interactions and emerging academic perspectives. It aims to broaden the understanding of museological concepts - particularly by proposing new approaches that transcend the epistemic limits often imposed by dominant paradigms and unilateral perspectives.